New geographical distribution and host records of rust fungi from northern Thailand - Jintana Engkhaninun (2018)
Ten species of rust fungi (Crossopsora 2, Maravalia 1, Pileolaria 1, Puccinia 1, Ravenelia 1, Sphaerophragmium 1, Uredo 2, and Uromyces 1) are newly recorded together with six new host plants in Thailand. © The Mycological Society of Japan and Springer-Verlag 2005.